PENGAPLIKASIAN TEKNIK MAKRAME PADA BUSANA LINGERIE SEBAGAI REPRESENTASI EKSPRESI DIRI - Allegra Qothrunnadaa Arifah Hafshoh; Kahfiati Kahdar (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2024)
The stigma related to lingerie in Indonesia is still focused on the perception of naughty clothing, rather than as a form of intimate and feminine expression, so local brand lingerie production is still not prominent. This research aims to investigate how much macrame techniques in lingerie design can meet the needs of self-expression and fashion innovation. This research uses design and development methods. Research data was taken from websites, scientific journals, e-books, reference books, Google forms, and direct observation. The research results show that integrating macrame techniques in lingerie design can fulfill the desire for femininity, producing aesthetic and functional products. This research concludes that lingerie design with this approach attracts market interest and creates new economic opportunities in the Indonesian market, elevating the concept of self-expression and femininity to a higher level.